Matemáticas, unidad sintética y a priori constitutivo - Pelaez, Alvaro (2007)
“Mathematics, synthetic unity and constitutive  a priori”. Startingfrom the emphasis about the kantian idea of the originary synthetic unity ofapperception like the basic function on which rest the production of all syntheticjudgment, in this paper I defend the idea of constitutive a priori of experienceunder the form of a similar synthetic principle but essentially formal, namely,the concept of transformation and group of transformations. To the same time,I try to show that Kant himself inspired, for articulate his own position, onmathematics, especially on synthetic geometry